PROTOTYPE OF A BOOK LENDING SYSTEM WITH AN RFID SCANNER MODULE USING AN ELECTRONIC KTP WITH TELEGRAM NOTIFICATIONS - Alvin D. Febriyanto; Randi Adzin Murdiantoro; Edmud Ucok Armin (Program Studi Teknik Elektro Universitas Peradaban, 2023)
Changes in information seeking behavior are one of the signs of the current development of science and information technology. This change has an impact on institutions engaged in information services and libraries. With a library, we can search, process, and store data that has turned into digital form. This research was conducted using the ADDIE method, which is a development from previous research. The stages of this research are by conducting several tests, namely rfid testing, testing the scanner module, sending rfid scan results to the web server, sending the scan module scan results to the web server and being able to make late notification notifications. The result of rfid reading efficiency is 76% with an rfid reading error value of 7.7%. Meanwhile, the efficiency of reading the scanner module was 80.6% with an error value of 5.5% for reading the scanner module. The prototype of the book lending system with rfid and the scanner module using an internet of things-based e-KTP succeeded in sending readings from the rfid and scanner module to a web server. This prototype also succeeded in sending notifications on borrowing and returning books, as well as notifications of delays and fines to users via telegram.